COMPLICATIONS OF THE LUNG ARTIFICIAL VENTILATION APPARATUS - Yovkochev D. SH.; Krasninkova M. B.; Kenjayev L. T. (Galaxy International Interdisciplinary Research Journal, 2024)
Currently, the development of the industry, the growth of man-made disasters and armed conflicts have significantly increased the number of victims with severe trauma, which is one of the main causes of disability and death of people of working age. Artificial lung ventilation (ventilator) is an integral part of the intensive care complex for all patients in critical condition, and in most cases it is not possible to avoid prosthetics of the respiratory function for victims with severe trauma.